Regarding the issue of developing creativity skills in future pedagogues - Abdurakhmanov Dilmurod Akramalievich (International Journal on Integrated Education, 2023)
Today's development of scientific knowledge, the impact of creativity on the development of the individual, society and the state requires a deep study of this issue from a scientific and pedagogical point of view. From this point of view, in this article, on the basis of a creative approach to education in educational and scientific research institutions, increasing the competitiveness of future pedagogues, influencing the educational process through creative approaches to educating mature pedagogues, and using innovative methodological developments , creativity, independent decision-making, initiative, Opinions on the improvement of interactive technologies in the development of patriotism and leadership qualities are presented.